Fracture Resistance of Anterior CAD/CAM Nanoceramic Resin Endocrowns with Different Preparation Designs - Badr, Aly Abdelkawy; Abozaid, Amira Ahmed; Wahsh, Marwa Mohamed; Morsi, Tarek Salah (Brazilian Dental Science, 2021)
Objective: The aim of the study was to evaluate the effect of extension of endocrown in pulp space and the effect of ferrule on the fracture resistance of anterior endocrowns made of nano-ceramic resin blocks. Material and Methods:  Twenty-eight freshly extracted human upper central incisor teeth were prepared to receive CAD/CAM nanoceramic resin endocrowns with four different designs. The specimens were divided into two groups (n = 14) according to the extension of the endocrown inside root canal (A:short and B:long), then each group was further subdivided into another two subgroups (n = 7) according to the presence or absence of ferrule effect (1:ferrule and 2: no ferrule).  Endocrowns were then fabricated using CEREC in lab and nanoceramic resin blocks (DENTSPLY Sirona, Germany) and LAVA ultimate (3M ESPE, Germany) blocks size 14L. Results: Two-way ANOVA showed that the ferrule (P > 0.0001) had statistically significant effect on the fracture resistance. However, the extension of the endocrown into the canal had no statistical significant effect on the fracture resistance (P = 0.837). The interactions between the independent variables (extension into the canal and ferrule) had statistically significant effect on the fracture resistance(P = 0.029). Load to fracture for group 1A was 439.53 N, 1B was 306.46 N, 2A was 516.29 N and 2B was 242.04 N. Conclusions:  Fracture resistance was not improved by the long or short extensions of the endocrowns in the pulp space, however, the ferrule effect shows significant improvement of the fracture resistance of the  nanoceramic resin endocrowns. Keywords Anterior endocrowns; Endocrown extensions; Fracture resistance; Nanoceramic resin blocks.